A novel vibration energy harvesting system integrated with an inertial pendulum for zero-energy sensor applications in freight trains. (15th July 2022) - Fang, Zheng; Tan, Xing; Liu, Genshuo; Zhou, Zijie; Pan, Yajia; Ahmed, Ammar; Zhang, Zutao
Graphical abstract: Fig. System Design of vibration energy harvesting system (VEHS). In this paper, a novel regenerative vibration energy harvesting system integrated with an inertial pendulum and a compact mechanical rectifier mechanism was developed for self-powered sensor applications in freight train monitoring systems. The proposed VEHS can capture the vibrations generated by wheel-rail coupling and turn them into electrical energy. It requires three main parts: energy input module, motion transformation module, and energy conversion module. The novel inertial pendulum was integrated with the energy input module to capture the vibration response of the bogie side frame. The compact mechanical rectifier mechanism converts the two-way rotations of the pendulum into one-way rotations of the generator to generate electricity. The dynamic response of the bogie system and VEHS was demonstrated through UM and Simulink. Then self-made prototype was used to study the performance of the system under different axle load and speed. The input angular velocity, output voltage, and output power of the proposed VEHS are positively correlated with the axle load and speed of the train, however the influence of the train speed is more significant. The energy harvesting efficiency of the system is directly related with the speed of the freight train, and the axle load has no significant effect on the efficiency. As the axle load and speed of the freight train increased, the RMS of the VEHS output voltage increased from 3.87 mV to 20.89 mV, the RMS of output power increased from 7.9 mW to 102.4 mW, and the energy harvesting efficiency increased from 35.24% to 68.29%. The peak output power of VEHS of 1.04W was achieved at an axle load of 27t, and the train speed of 120km/h. The application analysis of the Western Corridor of the China-Europe Railway based on the experimental data of VEHS also demonstrates the application of VEHS for the self-powered freight train monitoring system. Highlights: A novel high-efficiency vibration energy harvesting system (VEHS) is proposed. This VEHS collects vibration energy and powers the onboard monitoring system. A novel and compact mechanical rectification mechanism is integrated into the VEHS. The application and feasibility of the VEHS are analyzed based on China-Europe Express. The peak output power and efficiency of the VEHS are 1.04 W and 68.29 %. Abstract: With the development of the global economy, the demand for freight trains continues to rise, and the safety and maintenance of freight trains are essential. Therefore, sensors used for onboard monitoring of freight trains are vital components. However, the lack of onboard energy sources on freight trains makes the self-powering of sensors an urgent problem. In this paper, a novel renewable vibration energy harvesting system (VEHS) has been designed to provide electricity to sensors in freight train monitoring systems. The proposed VEHS mainly consists of three components: an energy input module, a motion transformation module, and an energy conversion module. The energy input module is composed of an inertial pendulum and a mass block. The movement transformation module integrates a novel and compact mechanical rectifier mechanism. The energy conversion module includes generators and energy storage devices. The wheel-rail coupled vibration is transformed into mechanical reciprocating rotation via the energy input module, and then into unidirectional mechanical rotation via the motion transformation module. Finally, the energy conversion module converts that mechanical energy of unidirectional rotation into electrical energy, and stores this micro-energy in a capacitor after rectification and boosting. Based on multi-body dynamics software and Simulink, a dynamic model was established to evaluate the vibration response of the system under different axle load and speed. Experiments revealed that the peak output power and energy harvesting efficiency of the VEHS were 1.04 W and 68.29 %, respectively. The RMS value of output power reaches 102.4 mW. In addition, this paper studies the application of the proposed VEHS to the China-Europe Express train. The results show that the system can be used to self-supply energy for freight train monitoring systems.